Alpha‐Fetoprotein Decrease from > 1, 000 to < 500 ng/mL in Patients with Hepatocellular Carcinoma Leads to Improved Posttransplant Outcomes. Issue 3 (10th February 2019) - Mehta, Neil; Dodge, Jennifer L.; Roberts, John P.; Hirose, Ryutaro; Yao, Francis Y.
Abstract : High alpha‐fetoprotein (AFP) > 1, 000 ng/mL is associated with poor outcomes after liver transplantation (LT) for hepatocellular carcinoma (HCC). A new national policy has been implemented for AFP > 1, 000 ng/mL requiring a decrease to < 500 ng/mL before LT, but there is a paucity of data on the optimal AFP threshold before LT. We aimed to evaluate the effects of a reduction in AFP from > 1, 000 ng/mL to different AFP thresholds before LT on survival and HCC recurrence after LT using the United Network for Organ Sharing database. We identified 407 patients who underwent transplant between January 2005 and September 2015 and who had AFP > 1, 000 ng/mL at least once before LT. The last AFP measurement before LT was > 1, 000 ng/mL in 72.0%, decreased from > 1, 000 to 101‐499 ng/mL in 9.6%, and decreased to ≤ 100 ng/mL in 14.3%. Local‐regional therapy was not performed in 45.4% of patients with AFP > 1, 000 ng/mL at LT versus 12.8% of those with AFP of 101‐499 ng/mL and 10.3% of those with AFP ≤ 100 ng/mL at LT ( P < 0.001). Kaplan‐Meier 5‐year post‐LT survival for those with AFP > 1, 000 ng/mL at LT was 48.8% versus 67.0% for those with a decrease in AFP to 101‐499 ng/mL ( P < 0.001) and 88.4% for those with AFP ≤ 100 ng/mL at LT ( P < 0.001). HCC recurrence probability at 5 years was 35.0% for patients with AFP > 1, 000 ng/mL versus 13.3% for patients with AFP of 101‐499 ng/mL and 7.2% for patients with AFP ≤ 100 ng/mL at LT ( P < 0.001). In multivariable analysis, a decrease in the AFP to 101‐499 ng/mL was associated with a > 2‐fold reduction in posttransplant mortality ( P = 0.01) and a nearly 3‐fold reduction in HCC recurrence ( P = 0.02) compared with AFP > 1, 000 ng/mL at LT. Conclusion : Our results demonstrated significantly improved post‐LT outcomes when restricting LT to patients with a reduction in AFP from > 1, 000 to < 500 ng/mL, validating the recently implemented national policy.